Analysis of Tax Avoidance and Firm Size on Fraudulent Financial Reporting with the Beneish M-Score Approach - Puspanita, Intan; Anistya Vinta Desi (Yayasan Ilomata, 2025)
This research investigated the impact of tax avoidance, firm size, and profitability on the F-Score as a measure of Fraudulent Financial Reporting (FFR) in Indonesian state-owned enterprises (BUMN). The use of the Beneish M-Score to detect fraud is not new, but applying it in the context of BUMN provides more insight into the level of honesty among government-linked businesses. The study utilizes secondary data from the annual financial statements of BUMN for the years 2019 to 2023 and employs multiple linear regression to examine the relationships among variables. The results indicated that tax avoidance exerts a positive and significant influence on FFR. It was implied that elevated levels of tax avoidance may enhance the probability of financial misstatement. On the other hand, the size and profitability of a company do not have a big impact on FFR. These results validate that tax evasion may serve as a preliminary indicator of possible financial reporting fraud. This study offers a contextual contribution to the Indonesian SOE sector and underscores the necessity of fortifying the theoretical framework that connects tax behavior to financial reporting errors. This study also offers practical recommendations for policymakers to enhance internal control systems and improve the transparency of taxation strategies for state-owned enterprises (SOEs).